Factors leading to sexual harassment of women in the workplace - Blanco, Mary Jane S.; Diaz, Mary Jane E.; Gallardo, May H.; Jacildo, Aileen Grace S.; Macabatao, Vener P. (1996.)
In undertaking this study, the researchers assumed that economic, socio-cultural, and psychological/mental/emotional factors leads to sexual harassment of women in the workplace and it in turn affects the psychological/mental emotional stability of the victim. Further, they also assumed that sexual harassment is rampant in the government sector. The researchers employed the random sampling method among private and government female employees working in Iloilo City. A total of 50 respondents were taken from an unknown population size. However, the sample size was reduced to 46 or 92% of the total sample size. Findings and results showed that sexual harassment cases are rampant in the private sector and socio-cultural factors often lead to sexual harassment of women in the workplace. However, economic and psycho-emotional factors were identified to cause sexual harassment whether directly or indirectly. Demographic factors like age, civil status, educational attainment and the job data were also determined to affect occurrence of sexual harassment of women in the workplace. Moreover, the number of women employed in an agency was found out to be the only significant determinant of sexual harassment.
Research Paper (BA 200 - Business Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 28, 1996.